2016
DOI: 10.1016/j.cyto.2015.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes mellitus coincident with pulmonary or latent tuberculosis results in modulation of adipocytokines

Abstract: Type 2 diabetes mellitus (T2DM) is recognized as major risk factor for the progress of active pulmonary tuberculosis (PTB), although the mechanistic link between diabetes and tuberculosis remains poorly characterized. Moreover, the influence of poorly controlled diabetes on the baseline levels of adipocytokines in the context of tuberculosis has not been explored in detail. To characterize the influence of coexistent DM on adipocytokine levels in pulmonary or latent TB (LTB), we examined circulating levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 42 publications
3
16
0
2
Order By: Relevance
“…In our published studies, we found that except for IL-22, all pro- and anti-inflammatory cytokine levels (Th1, Th2 and Th17) were significantly higher in the lungs of Mtb -infected T2DM mice than in the lungs of nondiabetic Mtb -infected mice [19]. Similar findings were noted in the plasma of T2DM TB patients compared with that of TB patients without T2DM [26,55]. Our current findings confirm these findings and further demonstrate that ILC3s are an important source of IL-22 in Mtb -infected mouse lungs, and defective IL-22 production by ILC3s in T2DM mice infected with Mtb leads to epithelial cell damage and enhanced mortality.…”
Section: Discussionmentioning
confidence: 56%
“…In our published studies, we found that except for IL-22, all pro- and anti-inflammatory cytokine levels (Th1, Th2 and Th17) were significantly higher in the lungs of Mtb -infected T2DM mice than in the lungs of nondiabetic Mtb -infected mice [19]. Similar findings were noted in the plasma of T2DM TB patients compared with that of TB patients without T2DM [26,55]. Our current findings confirm these findings and further demonstrate that ILC3s are an important source of IL-22 in Mtb -infected mouse lungs, and defective IL-22 production by ILC3s in T2DM mice infected with Mtb leads to epithelial cell damage and enhanced mortality.…”
Section: Discussionmentioning
confidence: 56%
“…This possibly happens through the activities of adipocytokines—cytokines produced by the adipose tissues of T2DM patients. Adipokines induce inflammatory processes in patients with T2DM and dysregulation of this cytokine has an impact on increased risk of developing LTBI in patients with T2DM [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adipose tissue is a central inflammatory source in obesity and type 2 DM, not only because of cytokines produced from the adipocyte itself, but also because of infiltration by pro‐inflammatory macrophages . To study the influence of DM on active PTB and LTB, Kumar et al . examined circulating levels of adipocytokines in the plasma of individuals with PTB‐DM or LTB‐DM and compared them with those without DM (PTB or LTB).…”
Section: Biomarkers Associated With Tb‐dm Co‐morbiditymentioning
confidence: 99%
“…In addition, adiponectin and adipsin display a significant negative correlation, whereas leptin, visfatin and plasminogen activator inhibitor‐1 (PAI‐1) show a significant positive correlation with HbA1C levels and random blood glucose levels. The authors suggest that alterations in the systemic levels of adipocytokines indicate that altered adipose tissue inflammation underlying type 2 DM potentially contributes to the pathogenesis of TB disease …”
Section: Biomarkers Associated With Tb‐dm Co‐morbiditymentioning
confidence: 99%